The Effects of Family Characteristics on the Return to Education - Altonji, Joseph G.; Dunn, Thomas A. (The Review of Economics and Statistics, 1996)
In this paper, the authors examine the role of parental education in the human capital production function by estimating the effects of parental education on the education profile of wages. The analysis uses sibling pairs from the Panel Study of Income Dynamics and the National Longitudinal Surveys of Labor Market Experience of Young Men and Young Women. The authors obtained mixed evidence on whether parental education raises the return to education. Copyright 1996 by MIT Press.